Medical clinic characteristics and access to behavioral health services for persons with HIV. - Ohl, Michael E; Landon, Bruce E; Cleary, Paul D; LeMaster, Joseph (Psychiatric services (Washington, D.C.), 2008)
Many persons with HIV do not receive needed behavioral health services. This study examined the impact of medical clinic characteristics on access to mental health and substance abuse care for persons with HIV.
Keywords: Adult; Ambulatory Care Facilities; Female; Follow-Up Studies; Health Services Accessibility; HIV Infections; Humans; Male; Medicine; Mental Disorders; Mental Health Services; Social Support; Specialization; Substance-Related Disorders; United States